Engineering coastal structures to centrally embrace biodiversity. (1st December 2022) - Suedel, Burton C.; Calabria, Jon; Bilskie, Matthew V.; Byers, James E.; Broich, Kelsey; McKay, S. Kyle; Tritinger, Amanda S.; Woodson, C. Brock; Dolatowski, Emily
Abstract: Global environmental factors (e.g., extreme weather, climate action failure, natural disasters, human environmental damage) increasingly threaten coastal communities. Shorelines are often hardened (seawalls, bulkheads) to prevent flooding and erosion and protect coastal communities. However, hardened shorelines lead to environmental degradation and biodiversity loss. Developmental pressures that are growing in scale, scope, and complexity necessitate the development of sustainable solutions to work with, rather than against, nature. Such nature-based solutions (NBS) provide protection and improve environmental quality and enhance biodiversity. To further this pressing need into action, the US Army Corps of Engineers (USACE) began the Engineering With Nature (EWN) initiative to balance economic, environmental, and social benefits through collaboration with partners and stakeholders. This work shows how engineering practice can be advanced through structured decision-making and landscape architecture renderings that include ecological sciences and NBS into an integrated approach for enhancing biodiversity in coastal marine environments. This integrated approach can be applied when designing new infrastructure projects or modifying or repairing existing infrastructure. To help communicate designs incorporating NBS, drawings, and renderings showcasing EWN concepts can aid decision-making. Our experiences with implementing EWN in practice have revealed that involving landscape architects can play a crucial role in successful collaboration and lead to solutions that protect coastal communities while preserving or enhancing biodiversity. Graphical abstract: Image 1 Highlights: Engineered coastal structures prevent flooding/erosion but can reduce biodiversity. Nature-based Solutions (NbS) provide flood protection and improve environmental quality. Resilient landscape architectural design can improve biodiversity with NbS. Engineering practice can be advanced through structured decision-making.